De la provincia Celtiberia a la qūrā de Santabariyya : arqueología de la antigüedad tardía en la provincia de Cuenca (siglos V-VIII d.C.) - Barroso Cabrera, Rafael, (Archaeopress Publishing Ltd, 2019)
This volume presents a historical and archaeological study of the province of Cuenca in Late Antiquity. The study concludes with an examination of the archaeological collection from the province, which has been divided into three large groups: monumental sculpture and epigraphic items, ceramic productions and metalwork arts.